Factors contributing to the prevalence of potential drug-drug interactions among hospitalized elderly patients in a tertiary hospital in Eastern Java, Indonesia - Faisal, Shah; Khotib, Junaidi; Wibisono, Cahyo; Hamidah, Khusnul Fitri; Utomo, Febriansyah Nur; Zairina, Elida (Medical Journal of Indonesia, 2025)
BACKGROUND Drug-drug interactions (DDIs) are the primary cause of adverse drug events. However, studies on potential DDIs (pDDIs) in hospitalized older adult patients in Indonesia remain limited. Therefore, this study aimed to investigate the prevalence and potential risk factors of pDDIs in this population. METHODS A prospective observational study assessing the medical profiles of hospitalized elderly patients was conducted at Universitas Airlangga Hospital from September 2023 to February 2024. Patient characteristics were recorded, and Micromedex® Drug-Reax software was used to check the pDDIs. Ethical approval was obtained for this study (No. 078/KEP/2023). Data were analyzed using SPSS software (version 26). RESULTS Of the 409 patients, 41.9% of the prescriptions contained pDDIs. Furthermore, 73 prescriptions (17.1%) had at least one pDDI, with 1–6 interactions per prescription. Of the 369 identified pDDIs, 209 (56.6%) were major interactions. Logistic regression analysis revealed increased odds of pDDIs in patients with previous medication use (adjusted odds ratio [aOR] = 2.254; crude odds ratio (cOR] = 1.771), polypharmacy (aOR = 16.309; cOR = 11.709), circulatory diseases (aOR = 4.082; cOR = 4.788), and genitourinary diseases (aOR = 1.819; cOR = 1.855). Conversely, patients with digestive system diseases had a significantly lower risk (aOR = 0.573; cOR = 0.608). CONCLUSIONS This study found a high prevalence of pDDIs (41.1%) among older hospitalized patients in Indonesia. Modifiable factors, such as polypharmacy and previous medication use, can reduce the risk of pDDIs and avoid adverse events.